Can Human Rights Violations Constitute Public Morals under the Article XX(a) of the GATT and Article XIV(a) of the GATS? - Rukhadze, Nino (Journal of Law, 2017)
The article considers the problem of interrelation between human rights and internationa trade law. The article studies whether human rights are banished from international trade law to such an extent that even fundamental human rights cannot be invoked by the Panel and the AB to challenge the public morals argument invoked by WTO members under the Article XX(a) of the General Agreement on Tariffs and Trade (hereinafter, GATT) and Article XIV(a) of the General Agreement of Trade in Services (hereinafter, GATS). The article maintains that international trade law doesn’t enable effective protection of human rights, since human rights law is not applicable in the World Trade Organization; moreover, the legal construction of the Article XX(a) of the GATT and the Article XIV(a) of the GATS do not ban trade restrictive measure, which contradicts human rights.